Professionalizing environmental education: outcomes from an undergraduate special topics course on environmental organizations and careers - Reamer, Marcus B. (Frontiers in Education, 2023)
In the modern workforce, environmental scholars and professionals need a working technical knowledge of complex social-environmental issues and a mastery of interpersonal skills like leadership, communication, and collaboration. This article reflects on a special topics course offered to undergraduate students in Fall 2021, titled “Survey of Environmental Organizations.” Pre- and post-course surveys were given to assess student experiences and outcomes. Results of paired t-tests and open-ended responses show that students gained confidence in their career prospects, developed and practiced professional skills, and benefitted from opportunities to network with professionals in their desired field(s). The principal contribution is a framework for educators who may want to integrate professional skills and career readiness into courses or programs in environmental science.